3(-2+2)=9a-10

Simple and best practice solution for 3(-2+2)=9a-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2+2)=9a-10 equation:


Simplifying
3(-2 + 2) = 9a + -10

Combine like terms: -2 + 2 = 0
3(0) = 9a + -10

Multiply 3 * 0
0 = 9a + -10

Anything times zero is zero.
0 = 9a + -10

Reorder the terms:
0 = -10 + 9a

Solving
0 = -10 + 9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9a' to each side of the equation.
0 + -9a = -10 + 9a + -9a
Remove the zero:
-9a = -10 + 9a + -9a

Combine like terms: 9a + -9a = 0
-9a = -10 + 0
-9a = -10

Divide each side by '-9'.
a = 1.111111111

Simplifying
a = 1.111111111

See similar equations:

| 2x+3x-12=4x-25 | | -127-8x=7x+23 | | 10+p=23 | | 3=10v-(-4v+1) | | k-13=18 | | 4x+6=-49-7x | | 3=10v-(4v+1) | | 75-3x=2x+15 | | 9+x=16 | | -1=-(3-8k)-k | | -8=-7m-(-3m+2) | | 6a-3(6-4a)=-6 | | 5x+78=11x+12 | | 65t=390 | | y-8=605 | | c-4=5 | | 18=b+9 | | 3(8n+2)+2=2-9n | | 5m-(-45k)+10m-10k= | | x+68=110 | | 3x^2-2=5x | | -5(-9a+3)=-4(-5-8a) | | n-5(n-3)=-n+6 | | -7-3x=3(3x+6) | | 12c^2+11c-15=0 | | 6x^2+13x-35=0 | | 12x^2+13x-35=0 | | 7-3m-6m=-20 | | 13-10x=46-31x | | 2p^2+5p-8=0 | | 3x+9=-51-7x | | -10z=.667 |

Equations solver categories